Short-term rheology of polycrystalline ice - Sinha, N. K. (1978)
Deformation characteristics of polycrystalline ice and their dependence on time, temperature, and stress have been analysed on the basis of a phenomenological relation which describes creep in terms of initial elastic, delayed elastic, and permanent strain. It is shown that the effective modulus of ice observed in the laboratory or in the field can be examined on the basis of this model. The model also provides a basis on which the observed flow law can be examined conveniently. Some apparent inconsistencies in the results of earlier investigations of the mechanical property of ice appear to be reconciled by the model. Les caractéristiques de déformation de la glace polycristalline et leur dépendence du temps, de la température et de la contrainte ont été analysées en utilisant une relation phénoménologique décrivant le fluage en terme de déformation élastique, déformation viscoélastique et dé formation plastique. On montre que le module effectif de la glace observé dans le laboratoire ou sur le terrain peut être considéré sur la base de ce modèle. Celui-ci fournit également les éléments permettant une analyse correcte de la loi d'écoulement expérimentale de la glace. Certaines contradictions apparentes dans les résultats des études antérieures concernant les propriétés mécaniques de la glace peuvent ainsi être dissipées. Peer reviewed: Yes NRC publication: Yes